Gender aspect of communicative behaviour of a human: verbal and non-verbal parameters of communication (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
Physiological and sociocultural preconditions for gender communication which realizes both by verbal and non-verbal means and forms gender stereotypes of communicative behaviour were analyzed in the article. The knowledge of such stereotypes is an important factor in efficient communication.
Keywords: communicative behavior; verbal and non-verbal communication parameters; gender communication; gender stereotypes; communication efficiency